The Ethyl Acetate Extract From Celastrus orbiculatus Promotes Apoptosis of Gastric Cancer Cells Through Mitochondria Regulation by PHB - Tao, Lide; Yin, Zixin; Ni, Tengyang; Chu, Zewen; Hao, Shihua; Wang, Zeyu; Sunagawa, Masataka; Wang, Haibo; Liu, Yanqing (Frontiers in Pharmacology, 2021)
Objective: To investigate the effect of ethyl acetate extract from Celastrus orbiculatus (COE) on gastric cancer cell apoptosis and reveal its underlying molecular mechanism. In addition, it was aimed to stablish a theoretical basis for the clinical application of Celastrus orbiculatus in the gastric cancer treatment. Material and Methods: Western blot and RT-qPCR were used to detect mRNA and protein expression of PHB in gastric cancer and adjacent tissues. MTT method was used to detect the COE effect on the proliferation of AGS cells and to determine the 50 % inhibitory concentration COE on these cells. COE effect on AGS apoptosis was evaluated by flow cytometry. Changes in apoptosis-related proteins expression in AGS cells were detected by western blot and changes in mitochondrial membrane potential were detected by JC-1 fluorescence staining. PHB expression was knocked down in AGS cells by lentiviral-mediated RNA interference. The COE antitumor effect was assessed in vivo using a subcutaneous transplantation tumor model in nude mice and in vivo fluorescence tracing technique in small animals. Results: The clinical samples analysis results showed that the PHB expression in gastric cancer samples was significantly higher than in corresponding adjacent tissues. MTT results showed that the AGS cell proliferation was significantly inhibited. RT-qPCR and western blot results showed that COE can significantly inhibit the PHB mRNA and protein expression, respectively. Flow cytometry analysis showed that COE was able to significantly promote AGS cell apoptosis. Western blot results also indicated that apoptosis-related protein expression changed significantly; BCL-2 expression significantly reduced while the Caspase-3 and Bax expression significantly increased after COE treatment. JC-1 fluorescence staining results showed that COE changed the mitochondrial membrane potential and activated the mitochondrial apoptosis pathway. Furthermore, in vivo experiments results demonstrated that the growth of subcutaneous transplanted tumor was significantly inhibited by the PHB knockdown and by the COE intragastric administration. Conclusion: COE can significantly promote apoptosis of human gastric cancer cells, which can be achieved by inhibiting PHB expression, thus altering the structure and function of mitochondria and activating the mitochondria apoptosis pathway. The antitumor effect of COE has also been proved in vivo.